Zero-preserving imputation of single-cell RNA-seq data - George C. Linderman; Jun Zhao; Manolis Roulis; Piotr Bielecki; Richard A. Flavell; Boaz Nadler; Yuval Kluger (Nature Communications, 2022)
Missing values in scRNA-seq datasets can bias their analysis. Here, the authors threshold the low rank approximation of the expression matrix, so false zeros can be imputed while true zeros are preserved.